2010
DOI: 10.6004/jnccn.2010.0020
|View full text |Cite
|
Sign up to set email alerts
|

Does Adjuvant Bisphosphonate in Early Breast Cancer Modify the Natural Course of the Disease? A Meta-Analysis of Randomized Controlled Trials

Abstract: To address whether the use of bisphosphonates in the adjuvant setting of breast cancer might have any effect on the natural course of the disease, a meta-analysis was conducted of published and unpublished randomized controlled trials found in PubMed, the Cochrane Central Register of Controlled Trials, the ISI Web of Knowledge, and abstracts of major international conferences up to January 2009. All trials that randomized patients with primary breast cancer to undergo adjuvant treatment with any bisphosphonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…The safety profile of this de-escalated treatment schedule of zoledronate was favourable and no new safety signal was observed compared to the adjuvant AZURE study using the identical treatment schedule [10]. The results are in concordance with the lack of effect of bisphosphonates reported for the adjuvant treatment of breast cancer, where no significant improvement of disease-free, bone disease-free and OS was observed in a literature-based meta-analysis involving 13 studies and 6885 patients [11]. Nevertheless the observed HR of 0.83 in patients over 55 years of age found in the NaTaN study is higher than in the AZURE study (HR 0.75 and 95% CI of 0.59e0.96) [12], but in line with findings from the most recent patient-based meta-analyses of the Early Breast Cancer Trialists' Collaborative Group including 18,766 patients, which found a significant improvement of DFS with a HR of 0.86 in the subgroup of postmenopausal patients [13].…”
Section: Discussionsupporting
confidence: 91%
“…The safety profile of this de-escalated treatment schedule of zoledronate was favourable and no new safety signal was observed compared to the adjuvant AZURE study using the identical treatment schedule [10]. The results are in concordance with the lack of effect of bisphosphonates reported for the adjuvant treatment of breast cancer, where no significant improvement of disease-free, bone disease-free and OS was observed in a literature-based meta-analysis involving 13 studies and 6885 patients [11]. Nevertheless the observed HR of 0.83 in patients over 55 years of age found in the NaTaN study is higher than in the AZURE study (HR 0.75 and 95% CI of 0.59e0.96) [12], but in line with findings from the most recent patient-based meta-analyses of the Early Breast Cancer Trialists' Collaborative Group including 18,766 patients, which found a significant improvement of DFS with a HR of 0.86 in the subgroup of postmenopausal patients [13].…”
Section: Discussionsupporting
confidence: 91%
“…A previous meta-analysis has shown that bisphosphonates did not lower breast cancer recurrence in the adjuvant setting, but a statistically significant lower risk for breast cancer recurrence was observed among patients receiving ZOL [28].…”
Section: Key Pointsmentioning
confidence: 93%
“…In patients with breast cancer and prostate cancer treated with hormone therapy (androgen deprivation or anastrozole, respectively), are reduced morbidity and osteopenia related to anti-neoplastic using pamidronate, clodronate, ZA, RIS and AL (91). While suspecting the possibilities, there is not enough clinical evidence to confirm a potential anti-tumor effect of ZA, requiring additional clinical trials to demonstrate this effect (92,93). The indication for use of BP should always be evaluated even when the patient moans pain or is at an early stage of the disease (94) because BP could have the important significance of maintaining bone health in patients with neoplastic disease and represent a complementary treatment for those in advanced stages (95).…”
Section: Other Advantages Of Bisphosphonate Therapymentioning
confidence: 99%